Rapid synthesis of long-chain deoxyribooligonucleotides by the N-methylimidazolide phosphotriester method. - Efimov, V A (1983)
A modified phosphotriester method has been employed for the efficient chemical synthesis of long-chain deoxyribooligonucleotides. During the course of this work, a general and rapid procedure was developed for the preparation of 24-62-mers in solution. Preparative reversed phase column chromatography on silanized silica gel was used to purify triester intermediates starting from 10-mers. The rapid synthesis of 32-mer and 42-mer on glass and silica gel supports using suitably protected 2-8-mer blocks as coupling units has been also accomplished. In particular, a convenient procedure for the solid-phase synthesis of oligonucleotide blocks bearing 3'-terminal phosphodiester groups is described.